PRESERVATION OF TRADITIONAL DANCE AS A MEDIUM OF EDUCATION AND IDENTITY OF THE INDONESIAN NATION - Sasmi, Desika Ayu; Hasan, Utari Zulfa (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2024)
This research aims to understand traditional dance as a medium of education and national identity in Indonesia. exploring how the digitalization of traditional dance can foster interest and love for the art of dance as an effort to preserve traditional dance as well as examining the contribution of traditional dance in building personal skills and fostering cultural understanding, this article highlights its potential as a medium for character representation, communication and cultural awareness. The importance of integrating multicultural information about local cultures into the education system to foster sensitivity to cultural diversity and foster a sense of pride in diverse cultural heritage. Traditional dance has an important role as a medium for conveying cultural, moral and historical values ??to the younger generation. Through distinctive movements and the meaning contained in each movement, traditional dance is able to teach about local wisdom, unity and cultural diversity which are an inseparable part of national identity. To ensure the sustainability of traditional dance arts as an inseparable part of the life and pride of the Indonesian nation.